Effects of xylanase and wheat middlings in diets for finishing pigs - Feoli, C.; Monge, C.R.; Jones, C.L.; Starkey, C.W.; Hancock, Joe D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 312 finishing pigs (average initial weight of 142 lb) were used in a 62-d experiment to determine the effects of xylanase and wheat middlings on growth performance, nutrient digestibility, and carcass characteristics. Treatments were a control diet based on corn-soybean meal, without and with 750 g/ton xylanase product (to supply none and 1,050 units of xylanase activity per lb of diet), and wheat middlings (none, 15%, and 30%) arranged as a 2 × 3 factorial. The pigs were sorted by sex and ancestry and blocked by weight, with 13 pigs/pen and 4 pens/treatment. Feed and water were provided on an ad libitum basis until the pigs were killed (average weight of 266 lb) at a commercial slaughter facility. Overall, there were no interactions among xylanase addition and concentration of wheat middlings in the diet for ADG, ADFI, F/G, dressing percentage, last-rib backfat thickness, or percentage carcass lean (P>0.26). For main effects, addition of xylanase did not change growth performance or carcass measurements (P>0.16), but, as concentration of wheat middlings was increased from none to 30%, there were linear decreases in overall ADG (P<0.003); efficiency of gain (P<0.002); hot carcass weight (P<0.001); dressing percentage (P<0.002); and digestibility of DM (P<0.001), N (P<0.04), and GE (P<0.001). Last-rib backfat thickness (P<0.06) decreased and percentage carcass lean increased (P<0.03) as wheat middlings concentration in the diet was increased from none to 30%. But these improvements in carcass leanness resulted from the light carcasses for pigs fed wheat middlings, and disappeared when hot carcass weight was used as a covariate (P>0.12). In conclusion, increasing the concentration of wheat middlings, in diets from none to 30% reduced growth performance and nutrient digestibility in finishing pigs. Addition of xylanase did not prevent these negative effects.
Keywords: Finishing pig; Wheat middlings; Xylanase; Swine